Education initiatives in cognitive debiasing to improve diagnostic accuracy in student providers: A scoping review. Issue 11 (7th November 2021) - Griffith, Patricia B.; Doherty, Caroline; Smeltzer, Suzanne C.; Mariani, Bette
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: The high prevalence of diagnostic errors by health care providers has prompted medical educators to examine cognitive biases and debiasing strategies in an effort to prevent these errors. The National Academy of Medicine hypothesized that explicit diagnostic reasoning education of all health care professionals can improve diagnostic accuracy. Objectives: The purpose of this scoping review is to identify, analyze, and summarize the existing literature on student health care providers' use of cognitive debiasing strategies to reduce diagnostic error. Data sources: The review was guided by the Joanna Briggs Institute methodology for scoping reviews. A systematic search of PubMed, CINAHL, PsychINFO, and Scopus databases for debiasing strategies in student provider education yielded 33 studies. Conclusions: The 33 studies included in this review represent four categories of debiasing strategies: increased medical knowledge or experience (seven studies), guided reflection (eight studies), self-explanation of reasoning (nine studies), and checklists to expand diagnosis considerations (seven studies). The studies were inclusive of medical students and residents; no studies included nurse practitioner (NP) students. Guided reflection, the most clearly defined and implemented strategy, showed the most promise for improvement of diagnostic accuracy. Educational interventions were wide ranging in content and delivery but did yield a path for future research. Implications for practice: There are myriad debiasing strategies student providers may use to mitigate cognitive bias. Structured reflection and education initiatives demonstrated the most consistent improvements in diagnostic accuracy. Future studies on debiasing strategies must include NP students to understand their response to these initiatives.